(3GdJjSjQ aj Yde GdbQGAGJs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI bGd GHh YeQh YKeGf GHf SYjO Hf YKeGf GdebQj GdMeO ddg GdeJaQO C(B/(3G HYO aEfce SCdJhfj Cf CUfa dce cJGHkG eNJUQkG aj ePGgH GdbQGA GdSHYI HGdCeUGQ s
(3BNQgG (B:s
(3hGSbWJ Cda GdhUd GdJj aj Chd QSe Gddg JYGdj aj LejY Pdc GSJZfGA YfgG s
(3HgG fXGe GdJYbjHIs
(3hHBNQg SeGYGJ hGLGRGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
Keywords: (3eJaQbGJs